2019
DOI: 10.1371/journal.pone.0215416
|View full text |Cite
|
Sign up to set email alerts
|

Investigating risk factors that predict a dog’s fear during veterinary consultations

Abstract: Attending the veterinary clinic is an integral part of the physical welfare of every companion dog. However, some dogs experience their veterinary visits negatively, which poses a risk of injury to the veterinary staff, their guardian (owner) and themselves. It may also influence the regularity of non-urgent veterinary appointments. To date there have been conflicting reports relating to the proportion of dogs that show fear during their veterinary visits. In this study, we explored the risk factors associated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…In contrast, Labrador Retrievers were seldomly fearful. These results are in agreement with previous studies, ranking mixed breed dogs high in fearfulness 9,13,35,40 and Labrador Retrievers and Staffordshire Bull Terriers low in fearfulness 35,41,45,46 . Fear of surfaces and heights was the most often observed in Rough Collie and mixed breed dogs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, Labrador Retrievers were seldomly fearful. These results are in agreement with previous studies, ranking mixed breed dogs high in fearfulness 9,13,35,40 and Labrador Retrievers and Staffordshire Bull Terriers low in fearfulness 35,41,45,46 . Fear of surfaces and heights was the most often observed in Rough Collie and mixed breed dogs.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, 17% of dogs showed fear of other dogs, 15% fear of strangers and 11% fear of novel situations. Prevalence of total fearfulness 12,16 and prevalence of fear subtraits 9,15,16,35 were quite similar in previous studies as well. Fear of surfaces and heights appears to be highly prevalent in our study population, as 23.5% of dog owners reported that their dogs were highly fearful of different surfaces and heights.…”
Section: Discussionsupporting
confidence: 86%
“…Considering the conflicting findings on the relationship between TRP and 5-HT peripheral levels, as well as the evidence on the effects of 5-HT on dog behaviour, the aim of this study was twofold: (1) to investigate the possible correlation between TRP and 5-HT serum concentrations in dogs that, differently from similar previous studies, were on a normal feeding regimen; (2) to assess potential differences in dogs’ TRP and 5-HT peripheral concentrations in relation to their behavioural response to a potentially stressful procedure, which in this case was represented by a veterinary examination [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…These can include low-stress handling methods, playing music, and suitable housing. This is an increasing area of research, and many resources are available by which staff can learn and practice these techniques (30)(31)(32)(33)(34)(35)(36)(37). Effective pharmacological interventions include trazodone, gabapentin, and transmucosal dexmedetomidine, as well as the use of pheromones (26,(38)(39)(40)(41)(42).…”
Section: Peri-operative Behavioral Managementmentioning
confidence: 99%